Ad'iyah al-Anbiya' Fi al-Qur'an al-Karim (Dirasah Tahliliyah Ma'aniyah) - Alwi, Itsnaini Muslimati (Arabiyatuna : Jurnal Bahasa Arab, 2019)
This study aims to describe and to determine the type of kalam in prophet supplications of al-Qur?an with its purpose. There are some verses in al-Qur?an containing prophet supplication.  The type of this research is descriptive qualitative. The source of data is the verses of prophet supplication in the holy Qur?an. The finding of this research show that the theme of prophet supplications in al-Qur?an are 63 times in 26 surat and 74 verses in al-Qur?an. The type of kalam in prophet supplications in al-Qur?an are two kinds, they are kalam khabar and kalam insya?. There are several purposes in each prophet supplication, the purpose of using kalam khabar are idzharu adh-dha?fi wal khusyu?i, tahriiqu al-himmah ila maa yalzamu tahshiluhu, al-istirham wa al-isti?thaf, al-fakhru, at-tadzkir bima baina al-murotib min at-tafaawut, idzhaaru at-tahassur, idzhaaru at-tahassur ?ala syaiin mahbuub, al-hatstsu ?ala as-sa?yi wa al-jiddi, al-madah, and at-takhdzir. And the purpose of using kalam insya? is ad-du?a.